Structural investigations in BaFe2 − xRuxAs2 as a function of Ru and temperature. Issue 1 (1st February 2015) - Sharma, Shilpam; Bharathi, A.; Vinod, K.; Sundar, C. S.; Srihari, V.; Sen, Smritijit; Ghosh, Haranath; Sinha, Anil K.; Deb, S. K.
<x xml:space="preserve">Abstract</x> We present the results of synchrotron X‐ray diffraction (XRD) measurements on powdered single‐crystal samples of BaFe2 − xRuxAs2, as a function of Ru content, and as a function of temperature, across the spin‐density wave transition in BaFe1.9Ru0.1As2. The Rietveld refinements reveal that with Ru substitution, while the a‐axis increases, the c‐axis decreases. In addition, the variation of positional coordinates of As (zAs), the Fe—As bond length and the As—Fe—As bond angles have also been determined. In the sample with x = 0.1, temperature‐dependent XRD measurements indicate that the orthorhombicity shows the characteristic increase with a decrease in temperature, below the magnetic transition. It is seen that the c‐axis, the As—Fe—As bond angles, Fe—As bond length and positional coordinates of the As show definite anomalies close to the structural transition. The observed anomalies in structural parameters are analysed in conjunction with restricted geometric optimization of the structure using ab initio electronic structure calculations.